Optical glass, glass preform, optical element and optical instrument

By optimizing the component ratio and process conditions of optical glass, the problem that existing optical glass is difficult to achieve high refractive index, low dispersion and large negative short wave relative partial dispersion is solved, and high performance and low cost optical glass preparation is achieved.

CN119263629APending Publication Date: 2025-01-07CDGM OPTICAL GLASS
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411408047.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

While existing optical glasses achieve high refractive index and low dispersion, it is difficult to effectively achieve large negative short wave relative partial dispersion, and commonly used high-field strength components such as Zr and Ta have stability and cost problems in the process.

Method used

Optical glass formulas with specific component ratios, including SiO2, B2O3, La2O3, Y2O3, ZnO, ZrO2, Nb2O5, etc., are designed with high refractive index, low dispersion and large negative shortwave relative parts by optimizing component ratios and process conditions. Dispersed optical glass.

Benefits of technology

The high refractive index, low dispersion and large negative short wave relative partial dispersion performance of optical glass are achieved, reducing design difficulty and production cost, while improving process stability and optical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005077222060000121
    Figure BDA0005077222060000121
  • Figure BDA0005077222060000122
    Figure BDA0005077222060000122
  • Figure BDA0005077222060000131
    Figure BDA0005077222060000131
Patent Text Reader

Abstract

The invention discloses optical glass with high refractive index, low dispersion and relatively large negative short wave relative partial dispersion. The optical glass comprises the following components in percentage by weight: 3-15% of SiO2; 24 to 34 percent of B2O3; 1 to 12 percent of La2O3; 7 to 16 percent of Y2O3; 20 to 30 percent of ZnO; zrO2: 3 to 9 percent; and 1 to 6 percent of Nb2O5. Through reasonable component design, the optical glass is good in production performance, and the optical glass has relatively high refractive index, relatively low dispersion and relatively large negative special dispersion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an optical glass, in particular to an optical glass with high refraction, low dispersion and negative short-wave relative partial dispersion, and a glass preform, an optical element and an optical instrument made of the same. Background Art

[0002] Optical glass with relatively high refractive index, relatively low dispersion, and large negative short-wave relative partial dispersion has significant application value in optical systems such as car cameras, digital cameras, and projectors. High refractive index and low dispersion glass lenses can form relatively small optical path differences for different colors of light while achieving refraction, which is beneficial to reducing the curvature and thickness of glass lenses for chromatic aberration correction, thereby improving the overall performance of the optical system and reducing the difficulty of design. If glass with a relatively high refractive index also has a large negative short-wave relative partial dispersion, it is beneficial to eliminate secondary chromatic aberration of the optical system on the basis of a smaller total length of the optical system.

[0003] There are two main ways to achieve large negative short-wave relative partial dispersion. The first way is to introduce a high-field strength component with a large mass ratio into the glass, and use the high-field strength component to modify the glass structure to achieve a large negative short-wave relative partial dispersion. Typical high-field strength components include Zr (zirconium), but Zr-containing raw materials are prone to form infusible materials during the melting process of glass batches, and excessive Zr content significantly reduces the process stability of the glass. If the difficulty of chemical synthesis of Zr is improved by increasing the melting temperature, defects such as platinum flash point may easily appear in the glass. The use of solid-phase reaction to prepare Zr-containing multinary oxides (such as SiZrO4) is beneficial to improving the difficulty of chemical synthesis of Zr-containing raw materials, but this method has large equipment occupancy, high energy consumption, and is prone to the introduction of impurities, which is not conducive to the industrial mass production of optical glass. The second way is to introduce components with high refractive index contribution, such as Ta (tantalum) and Nb (niobium), into the glass at a large mass ratio, so that the glass can contain as many components with low refractive index contribution and shorter UV absorption characteristic wavelength as possible, such as boron and silicon, on the basis of a certain glass refractive index, thereby achieving negative short-wave relative partial dispersion. However, Ta, Nb, etc. are low-abundance element components, and the raw materials are expensive, which is not conducive to improving the cost performance of optical glass. Summary of the invention

[0004] Based on the above reasons, the technical problem to be solved by the present invention is to provide an optical glass with high refractive index, low dispersion and large negative short-wave relative partial dispersion.

[0005] The technical solution adopted by the present invention to solve the technical problem is:

[0006] Optical glass, whose components are expressed in weight percentage, contains: SiO2: 3~15%; B2O3: 24~34%; La2O3: 1~12%; Y2O3: 7~16%; ZnO: 20~30%; ZrO2: 3~9%; Nb2O5: 1~6%.

[0007] Furthermore, the optical glass, whose components are expressed in weight percentage, also contains: Al2O3: 0-8%; and / or Gd2O3: 0-12%; and / or Li2O: 0-4%; and / or Na2O: 0-5%; and / or K2O: 0-5%; and / or MgO: 0-5%; and / or CaO: 0-5%; and / or SrO: 0-5%; and / or BaO: 0-4%; and / or Ta2O5: 0-5%; and / or WO3: 0-3%; and / or Sb2O3: 0-0.5%.

[0008] Optical glass, whose components are expressed in weight percentage, consists of SiO2: 3~15%; B2O3: 24~34%; La2O3: 1~12%; Y2O3: 7~16%; ZnO: 20~30%; ZrO2: 3~9%; Nb2O5: 1~6%; Al2O3: 0~8%; Gd2O3: 0~12%; Li2O: 0~4%; Na2O: 0~5%; K2O: 0~5%; MgO: 0~5%; CaO: 0~5%; SrO: 0~5%; BaO: 0~4%; Ta2O5: 0~5%; WO3: 0~3%; Sb2O3: 0~0.5%.

[0009] Furthermore, the components of the optical glass are expressed in weight percentage, wherein: Al2O3+B2O3+SiO2 is 35-45%, preferably Al2O3+B2O3+SiO2 is 36-44%, and more preferably Al2O3+B2O3+SiO2 is 37-43%.

[0010] Furthermore, the optical glass has components expressed in weight percentage, wherein:

[0011] B2O3 / (SiO2+Al2O3) is 1.5 to 4.0, preferably B2O3 / (SiO2+Al2O3) is 1.6 to 3.8, and more preferably B2O3 / (SiO2+Al2O3) is 1.8 to 3.6.

[0012] Furthermore, the optical glass has components expressed in weight percentage, wherein:

[0013] (Al2O3+ZrO2) / (Al2O3+B2O3+SiO2) is 0.085~0.375, preferably (Al2O3+ZrO2) / (Al2O3+B2O3+SiO2) is 0.100~0.325, and more preferably (Al2O3+ZrO2) / (Al2O3+B2O3+SiO2) is 0.125~0.300.

[0014] Furthermore, the components of the optical glass are expressed in weight percentage, wherein: Y2O3 / (2×ZnO+B2O3) is 0.090~0.210, preferably Y2O3 / (2×ZnO+B2O3) is 0.110~0.205, and more preferably Y2O3 / (2×ZnO+B2O3) is 0.130~0.200.

[0015] Furthermore, the components of the optical glass are expressed in weight percentage, wherein: Gd2O3+Y2O3 is 13-22%, preferably Gd2O3+Y2O3 is 14-21%, and more preferably Gd2O3+Y2O3 is 15-20%.

[0016] Furthermore, the components of the optical glass are expressed in weight percentage, wherein: (2×Li2O+SiO2) / ZrO2 is 0.800~5.0, preferably (2×Li2O+SiO2) / ZrO2 is 0.850~4.5, and more preferably (2×Li2O+SiO2) / ZrO2 is 0.900~4.0.

[0017] Furthermore, the optical glass has components expressed in weight percentage, wherein:

[0018] (Nb2O5+Ta2O5+WO3) / (La2O3+ZrO2) is 0.05~0.65, preferably (Nb2O5+Ta2O5+WO3) / (La2O3+ZrO2) is 0.05~0.55, and more preferably (Nb2O5+Ta2O5+WO3) / (La2O3+ZrO2) is 0.05~0.45.

[0019] Furthermore, the optical glass, its components are expressed in weight percentage, wherein: SiO2: 4-14%, preferably SiO2: 5-13%; and / or B2O3: 25-33%, preferably B2O3: 26-32%; and / or La2O3: 2-10%, preferably La2O3: 3-8%; and / or Y2O3: 8-15%, preferably Y2O3: 9-14%; and / or ZnO: 21-28%, preferably ZnO: 22-26%; and / or ZrO2: 3.5-8.5%, preferably ZrO2: 4-8%; and / or Nb2O5: 1.5-5.5%, preferably Nb2O5: 2-5%; and / or Al2O3: 0.5-6%, Preferred Al2O3: 1-4%; and / or Gd2O3: 0.5-9%, preferably Gd2O3: 1-6%; and / or Li2O: 0.05-3%, preferably Li2O: 0.1-2%; and / or Na2O: 0-3%, preferably Na2O: 0-1%; and / or K2O: 0-2%; and / or MgO: 0-2%; and / or CaO: 0-2%; and / or SrO: 0-2%; and / or BaO: 0-3%, preferably BaO: 0-2%; and / or Ta2O5: 0-2%; and / or WO3: 0-1.5%, preferably WO3: 0.1-1%; and / or Sb2O3: 0-0.3%, preferably Sb2O3: 0-0.2%.

[0020] Further, the optical glass does not contain K2O; and / or does not contain MgO; and / or does not contain CaO; and / or does not contain SrO; and / or does not contain Ta2O5; and / or does not contain Bi2O3; and / or does not contain TiO2; and / or does not contain P2O5; and / or does not contain GeO2; and / or does not contain TeO2; and / or does not contain Tl2O; and / or does not contain CdO; and / or does not contain As2O3; and / or does not contain PbO; and / or does not contain Cl - ; and / or does not contain F - ; and / or does not contain S 2- .

[0021] Furthermore, the refractive index n of the optical glass is d 1.70 to 1.75, preferably 1.71 to 1.74; and / or Abbe number ν d 43 to 48, preferably 44 to 47.5; and / or short-wave partial dispersion P g,F is 0.5600 or less, preferably 0.5590 or less, more preferably 0.5580 or less; and / or the short-wave relative partial dispersion ΔP g,F It is -0.0075 or less, preferably -0.0080 or less, and more preferably -0.0085 or less.

[0022] Furthermore, the λ of the optical glass 80 is 370nm or less, preferably 365nm or less, more preferably 360nm or less; and / or λ5 is 330nm or less, preferably 325nm or less, more preferably 320nm or less; and / or water resistance stability R W Class 1 and the water leaching resistance percentage is less than 0.04%, preferably Class 1 and the water leaching resistance percentage is below 0.03%, more preferably Class 1 and the water leaching resistance percentage is below 0.02%; and / or acid resistance stability R A 4 or more, preferably 3 or more; and / or density ρ is 4.05 g / cm 3 Below, preferably 4.00 g / cm 3 Below, more preferably 3.95g / cm 3 Below; and / or thermal expansion coefficient α -30~70℃ 60×10 -7 / ℃ or less, preferably 58×10 -7 / °C or less, more preferably 56×10 -7 / ℃ or below; and / or thermal expansion coefficient α 100~300℃ 70×10 -7 / ℃ or less, preferably 67×10 -7 / °C or less, more preferably 64×10 -7 / ℃ or below; and / or micro Vickers hardness H v 670×10 7 Pa or more, preferably 690×10 7 Pa or more, more preferably 710×10 7 Pa or above; and / or transition temperature T g The temperature is 540-630°C, preferably 550-620°C, more preferably 560-610°C; and / or the anti-thermal forming crystallization performance is 3 or more, preferably 2 or more, more preferably 1; and / or the anti-crystallization performance is 3 or more, preferably 2 or more; and / or the bubble degree is A0 or more, preferably A 00 and / or a refining temperature of 1260°C or less, preferably 1240°C or less, more preferably 1220°C or less.

[0023] The glass preform is made of the above optical glass.

[0024] The optical element is made of the above optical glass or the above glass preform.

[0025] An optical instrument containing the above optical glass or the above optical element.

[0026] The beneficial effects of the present invention are: through reasonable component design, the production performance of the optical glass of the present invention is good, and the optical glass of the present invention has a relatively high refractive index, a relatively low dispersion and a large negative short-wave relative partial dispersion. DETAILED DESCRIPTION

[0027] Below, the embodiments of the optical glass of the present invention are described in detail, but the present invention is not limited to the following embodiments, and can be implemented by appropriate changes within the scope of the purpose of the present invention. In addition, although there are appropriate omissions of descriptions of the repeated descriptions, the main purpose of the invention will not be limited thereby. In the following content, the optical glass of the present invention can be referred to as glass.

[0028] [Optical glass]

[0029] The following is an explanation of the range of each component of the optical glass of the present invention. In this specification, unless otherwise specified, the content, total content, and total content of each component are all expressed in weight percentage relative to the total amount of glass material converted into oxide composition. Here, the "composition converted into oxide" means that when the oxides, composite salts, hydroxides, etc. used as raw materials for the optical glass components of the present invention decompose and transform into oxides during melting, the total amount of the oxide material is taken as 100%.

[0030] Unless otherwise indicated in specific circumstances, the numerical ranges listed herein include upper and lower limits, "above" and "below" include the endpoints, and all integers and fractions included in the range, without being limited to the specific values ​​listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.

[0031] The "short-wave relative partial dispersion" referred to in this article refers to the deviation of the short-wave dispersion of glass from the normal curve of optical glass. The "increase of short-wave relative partial dispersion" or "improvement of short-wave relative partial dispersion" referred to in this article refers to the increase or improvement of the difference between the short-wave relative partial dispersion value and zero.

[0032] <Essential Components and Optional Components>

[0033] B2O3 is an essential component of the optical glass of the present invention. B2O3 can form two glass network structures [BO3] and [BO4] in the glass, among which the ultraviolet absorption peak wavelength of the [BO3] structure is shorter, and the [BO3] structure is the main source of negative short-wave relative partial dispersion. The increase in the content of B2O3 is conducive to the optimization of the anti-crystallization performance of the glass of the present invention. At the same time, the glass with B2O3 as the main network former can maintain good crystallization performance when containing more La2O3, Y2O3, Gd2O3, and ZnO components. When the B2O3 content is within a certain range, it is easy to achieve the short-wave relative partial dispersion performance of the glass of the present invention. However, if the B2O3 content is too high, in order to achieve the glass refractive index within the required range of the glass of the present invention, it is bound to lead to an increase in the content of high-cost components such as Nb2O5 and Ta2O5, thereby increasing the cost of the glass. Therefore, the content of B2O3 in the present invention is 24-34%, preferably 25-33%, and more preferably 26-32%.

[0034] ZnO is an essential component of the optical glass of the present invention. ZnO is beneficial to improving the anti-crystallization performance and anti-thermal forming crystallization performance of the glass. An increase in the ZnO content is beneficial to improving the negative short-wave relative partial dispersion of the glass of the present invention. However, too high a ZnO content will make it difficult for the glass of the present invention to have a high refractive index while ensuring good anti-crystallization performance and a high Abbe number. Therefore, the ZnO content is 20-30%, preferably 21-28%, and more preferably 22-26%.

[0035] SiO2 is an essential component of the glass of the present invention. SiO2 can improve the resistance to devitrification and thermal stability of the glass. However, if the SiO2 content in the glass is too high, the high-temperature viscosity of the glass will be too high, resulting in an increase in the glass clarification temperature and a tendency to deteriorate the melting properties of the raw materials constituting the glass. Therefore, the content of SiO2 is 3 to 15%, preferably 4 to 14%, and more preferably 5 to 13%.

[0036] The network structures that Al2O3 can form in glass include [AlO4] and [AlO6], among which [AlO4] is negatively charged and is generally formed in the presence of free oxygen. Al2O3 can consume free oxygen in the glass, increasing the possibility of B2O3 in the glass forming a [BO3] structure, thereby blue-shifting the ultraviolet characteristic absorption wavelength of the glass and reducing the short-wave relative partial dispersion of the glass. The inventors have found through a large number of experimental studies that increasing the content of Al2O3 can significantly reduce the short-wave relative partial dispersion of the glass. At the same time, the increase in the content of Al2O3 is beneficial to improving the connection degree of the glass network when the content of glass network intermediates is high, which is beneficial to reducing the thermal expansion coefficient of the glass, increasing the Vickers hardness, and achieving a higher refractive index when the glass density is low. However, if the content of Al2O3 is too high, the anti-thermal forming crystallization performance of the glass will decrease. Therefore, the content of Al2O3 is 0-8%, preferably 0.5-6%, and more preferably 1-4%.

[0037] The inventors have found through a large number of experimental studies that the total content of Al2O3, B2O3, and SiO2 in the glass, Al2O3+B2O3+SiO2, is too high or too low, which leads to a decrease in the negative short-wave relative partial dispersion of the glass. Therefore, in some embodiments, Al2O3+B2O3+SiO2 is preferably 35-45%, more preferably Al2O3+B2O3+SiO2 is 36-44%, and further preferably Al2O3+B2O3+SiO2 is 37-43%. When the content of Al2O3+B2O3+SiO2 is within the above preferred range, it is easy to achieve a larger negative short-wave relative partial dispersion.

[0038] The inventors have found through a large number of experimental studies that the change in the ratio B2O3 / (SiO2+Al2O3) between the content of B2O3 and the total content of SiO2 and Al2O3 (SiO2+Al2O3) has a significant impact on the production performance of glass. If the value of B2O3 / (SiO2+Al2O3) is too large, the glass will volatilize more during the clarification and homogenization process, and too much volatiles will be deposited on the top of the furnace and randomly fall into the glass liquid, which is not conducive to maintaining the consistency of the glass refractive index; if the value of B2O3 / (SiO2+Al2O3) is too small, the surface tension of the glass liquid is too large, and the available clarification temperature is too high, which also leads to a large amount of volatilization of the glass during the clarification and homogenization process, which is not conducive to maintaining the consistency of the glass refractive index. Therefore, preferably B2O3 / (SiO2+Al2O3) is 1.5 to 4.0, more preferably B2O3 / (SiO2+Al2O3) is 1.6 to 3.8, and further preferably B2O3 / (SiO2+Al2O3) is 1.8 to 3.6. Within the above preferred range, the glass has a suitable viscosity and good anti-crystallization performance.

[0039] ZrO2 is an essential component of the glass of the present invention. ZrO2 can improve the hardness, refractive index and chemical stability of optical glass, and reduce the thermal expansion coefficient of glass. However, as the content of ZrO2 increases, the unevenness in the melting process of the glass batch becomes obvious, which increases the difficulty of producing optical glass with high uniformity; if the content of ZrO2 further increases, the glass requires a higher temperature to achieve homogenization, which affects the life of refractory materials or platinum utensils; if the content of ZrO2 further increases, Zr-rich paste precipitates are prone to appear in the glass, the process difficulty increases sharply, and it is difficult to obtain high-quality optical glass. Therefore, the content of ZrO2 is 3-9%, preferably 3.5-8.5%, and more preferably 4-8%.

[0040] The inventors have found through a large number of experimental studies that if the value of (Al2O3+ZrO2) / (Al2O3+B2O3+SiO2) is too high, the anti-crystallization performance of the glass will deteriorate, which may easily lead to quality problems such as the presence of tiny crystallization particles in the glass; if the value of (Al2O3+ZrO2) / (Al2O3+B2O3+SiO2) is too low, the short-wave relative partial dispersion of the glass will be difficult to reach the expected value. Therefore, it is preferred that (Al2O3+ZrO2) / (Al2O3+B2O3+SiO2) is 0.085 to 0.375, more preferably (Al2O3+ZrO2) / (Al2O3+B2O3+SiO2) is 0.100 to 0.325, and further preferably 0.125 to 0.300. (Al2O3+ZrO2) / (Al2O3+B2O3+SiO2) Within the above preferred range, the glass has better anti-crystallization performance and desired short-wave relative partial dispersion, as well as a lower thermal expansion coefficient and a higher Vickers hardness.

[0041] Y2O3 is an essential component of the glass of the present invention. The higher the content of Y2O3, the easier it is to achieve high refractive index and low dispersion performance. At the same time, Y2O3 can also improve the elastic modulus of the glass. When the Y2O3 content is within a certain range, the thermal expansion coefficient of the glass tends to decrease. Among the components that can achieve high refractive index and low dispersion, the cost of Y2O3 is relatively low. However, if the Y2O3 content is too high, the anti-crystallization performance of the glass will be seriously deteriorated. Therefore, the content of Y2O3 is 7-16%, preferably 8-15%, and more preferably 9-14%.

[0042] In some embodiments, by controlling Y2O3 / (2×ZnO+B2O3) within a certain range, the glass has good anti-crystallization performance while ensuring that the optical properties of the glass reach the target value of the present invention. In some embodiments, if Y2O3 / (2×ZnO+B2O3) is low, in order to achieve the characteristics of the glass of the present invention, the content of Gd2O3 in the glass needs to be increased, and Gd2O3 is a precious oxide component. A high content of Gd2O3 will increase the cost of the glass. If Y2O3 / (2×ZnO+B2O3) is too low, it is difficult for the optical properties of the glass to reach the target value of the present invention; if Y2O3 / (2×ZnO+B2O3) is too high, the anti-crystallization performance of the glass is difficult to meet production requirements. Therefore, it is preferred that Y2O3 / (2×ZnO+B2O3) is 0.090 to 0.210, more preferably 0.110 to 0.205, and further preferably 0.130 to 0.200. On the other hand, Y2O3 / (2×ZnO+B2O3) being within the above preferred range is also beneficial for the glass transition temperature of the glass to be within an appropriate range.

[0043] The glass of the present invention contains a proper amount of Gd2O3, which is beneficial to improving the anti-crystallization performance of the glass. However, if the content of Gd2O3 is too high, the surface crystallization tendency of the glass increases. At the same time, Gd2O3 is a relatively expensive component, and the raw material cost of the glass increases when the content is high. Therefore, the content of Gd2O3 is 0 to 12%, preferably 0.5 to 9%, and more preferably 1 to 6%.

[0044] Gd2O3 and Y2O3 play a key role in whether the optical glass can achieve the relatively high refractive index and relatively large Abbe number optical properties expected by the present invention. If the combined content of Gd2O3+Y2O3 is too low, it is difficult to achieve the relatively high refractive index and relatively large Abbe number expected by the present invention; however, if Gd2O3+Y2O3 is too high, it is difficult for the glass to maintain the excellent anti-crystallization performance. Therefore, it is preferred that Gd2O3+Y2O3 is 13-22%, more preferably Gd2O3+Y2O3 is 14-21%, and further preferably Gd2O3+Y2O3 is 15-20%. On the other hand, when Gd2O3+Y2O3 is within the above preferred range, the density of the glass is relatively low.

[0045] La2O3 is an essential component of the glass of the present invention. La2O3 can increase the refractive index of the glass. At the same time, the cost of La2O3 raw materials is relatively low. Increasing the La2O3 content as much as possible is beneficial to improving the cost performance of high refractive index optical glass. Compared with Y2O3, an increase in the La2O3 content is less likely to cause the anti-crystallization performance of the glass to deteriorate. However, too high a La2O3 content is not conducive to achieving the short-wave relative partial dispersion properties of the glass of the present invention. Therefore, the content of La2O3 is 1 to 12%, preferably 2 to 10%, and more preferably 3 to 8%.

[0046] Nb2O5 can improve the refractive index and dispersion of glass, and is an essential component of the glass of the present invention. Nb2O5 is a high field strength component, which is beneficial for B2O3 in the glass to exist in a [BO3] coordination structure. An appropriate amount of Nb2O5 is beneficial for increasing the content of B2O3 in the glass under a certain refractive index. However, too high a content of Nb2O5 will lead to an increase in the cost of optical glass raw materials, and is not conducive to the glass obtaining a lower dispersion. Therefore, the content of Nb2O5 is 1 to 6%, preferably 1.5 to 5.5%, and more preferably 2 to 5%.

[0047] The inventors have found through research that when Li2O is present in the glass of the present invention, the anti-crystallization performance of the glass, especially the ability to resist the precipitation of ZrO2-rich crystals, is significantly improved. However, an increase in the Li2O content will lead to a decrease in the chemical stability and hardness of the glass. Within a certain range, the Li2O content does not affect the thermal expansion coefficient of the glass of the present invention. When the Li2O content is too high, the optical properties of the glass, such as the refractive index, Abbe number, and short-wave relative partial dispersion, are difficult to reach the design values ​​of the present invention. Therefore, the content of Li2O is 0 to 4%, preferably 0.05 to 3%, and more preferably 0.1 to 2%.

[0048] The inventors have found through a large number of experimental studies that when ZrO2 is used as a raw material to make the glass contain ZrO2, in the glass of the present invention, ZrO2 only reacts with Li2O and SiO2 in a solid phase reaction. Since the chemical properties of ZrO2 are stable, this solid phase reaction is very meaningful for the process of vitrification of the ZrO2 raw material. Furthermore, the inventors have found that if (2×Li2O+SiO2) / ZrO2 is too small, on the one hand, the vitrification rate is slow, and residual ZrO2 infusible materials are likely to exist, resulting in a deterioration in the intrinsic quality of the glass, and on the other hand, the anti-crystallization performance of the glass is reduced. If (2×Li2O+SiO2) / ZrO2 is too large, the chemical stability of the glass will deteriorate and the short-wave relative partial dispersion will decrease. Therefore, in the present invention, (2×Li2O+SiO2) / ZrO2 is preferably 0.800 to 5.0, (2×Li2O+SiO2) / ZrO2 is more preferably 0.850 to 4.5, and (2×Li2O+SiO2) / ZrO2 is further preferably 0.900 to 4.0.

[0049] Na2O is an optional component of the glass of the present invention. Na2O can reduce the melting temperature and clarifying temperature of the glass. However, in the glass of the present invention, the use of Na2O is likely to lead to deterioration of the glass's anti-thermal forming crystallization performance. Therefore, the content of Na2O is 0-5%, preferably 0-3%, and more preferably 0-1%.

[0050] K2O is an optional component of the glass of the present invention. K2O helps to lower the clarification temperature of the glass and increase the melting rate, but in the glass of the present invention, an increase in the K2O content will cause a significant decrease in the anti-devitrification performance of the glass. Therefore, the content of K2O is 0-5%, preferably 0-2%, and more preferably no K2O is contained.

[0051] MgO is an optional component of the glass of the present invention. MgO is beneficial to improving the chemical stability of the glass. However, too high a MgO content is not conducive to obtaining the desired optical properties of the glass of the present invention, and also leads to the deterioration of the anti-crystallization performance of the glass. Therefore, the content of MgO is 0 to 5%, preferably 0 to 2%, and more preferably no MgO is contained.

[0052] CaO is an optional component of the glass of the present invention. CaO is beneficial to improving the chromaticity and mechanical properties of the glass, but a high content of CaO is not conducive to obtaining the desired optical properties of the glass of the present invention. Therefore, the content of CaO is 0 to 5%, preferably 0 to 2%, and more preferably no CaO is contained.

[0053] SrO is an optional component of the glass of the present invention. The role of SrO in glass is similar to that of MgO and CaO. The appropriate content of SrO does not affect the anti-devitrification performance of the glass. However, a high content of SrO is not conducive to obtaining the desired optical properties of the glass of the present invention. Therefore, the content of SrO is 0 to 5%, preferably 0 to 2%, and more preferably no SrO is contained.

[0054] BaO is an optional component of the glass of the present invention. BaO has the function of increasing the refractive index of the glass, and a small amount of BaO does not affect the anti-devitrification performance of the glass. However, when the BaO content is too high, the melting process of the glass raw materials becomes difficult, and a higher melting temperature is required, resulting in a deterioration of the internal transparency of the glass. Therefore, the content of BaO is 0 to 4%, preferably 0 to 3%, and more preferably 0 to 2%.

[0055] Ta2O5 is an optional component of the glass of the present invention. Ta2O5 can increase the refractive index of the glass, but its raw material price is expensive, and a high content is not conducive to reducing the cost of the glass. Therefore, the content of Ta2O5 is 0-5%, preferably 0-2%, and more preferably no Ta2O5 is contained.

[0056] In the present invention, by containing 0-3% WO3, the glass can have a desired refractive index and excellent anti-crystallization performance and bubble degree. Therefore, the content of WO3 is 0-3%, preferably 0-1.5%, and more preferably 0.1-1%.

[0057] Nb2O5, Ta2O5, and WO3 are high-cost components with low abundance in the earth's crust. From the perspective of reducing the use of high-cost raw materials and reducing the environmental pressure of glass production, the content of the above three components should be reduced. However, in order to achieve the excellent performance of the glass of the present invention, the inventors have found through a large number of experimental studies that controlling (Nb2O5+Ta2O5+WO3) / (La2O3+ZrO2) within the range of 0.05 to 0.65 can ensure the optical constants of the glass while making the glass have excellent bubble degree and thermal expansion coefficient. Therefore, the preferred ratio of (Nb2O5+Ta2O5+WO3) / (La2O3+ZrO2) is 0.05 to 0.65, the more preferred ratio of (Nb2O5+Ta2O5+WO3) / (La2O3+ZrO2) is 0.05 to 0.55, and the further preferred ratio of (Nb2O5+Ta2O5+WO3) / (La2O3+ZrO2) is 0.05 to 0.45.

[0058] Sb2O3 acts as a clarifier in glass and has the effect of increasing the bubble degree of glass. However, the presence of Sb2O3 in glass will significantly reduce the short-wave relative partial dispersion of the glass, making it difficult for the glass of the present invention to have a large negative short-wave relative partial dispersion. In particular, in the absence of Sb2O3, the glass of the present invention can still have a good clarification effect due to its low viscosity. Therefore, the content of Sb2O3 is in the range of 0 to 0.5%, preferably 0 to 0.3%, and more preferably 0 to 0.2%.

[0059] <Ingredients not contained>

[0060] Bi2O3 is a high refractive index component, but Bi2O3 in glass has the property of significantly reducing the short-wave relative partial dispersion of glass, and the presence of Bi2O3 increases the difficulty of glass processing. Therefore, the glass of the present invention preferably does not contain Bi2O3.

[0061] TiO2 is a high refractive index and high dispersion component. A proper amount of TiO2 helps improve the anti-devitrification performance of the glass. However, the presence of TiO2 significantly makes the short-wave relative partial dispersion of the glass tend to be positive. Therefore, the glass of the present invention preferably does not contain TiO2.

[0062] P2O5 is a glass network former component. Although P2O5 has the effect of lowering the melting temperature of glass and increasing the ultraviolet transmittance of glass, the inclusion of P2O5 in glass will significantly lead to a positive tendency of the short-wave relative partial dispersion of glass. Therefore, the glass of the present invention preferably does not contain P2O5.

[0063] GeO 2 and TeO 2 are expensive raw materials. In some embodiments, it is preferred that GeO 2 and / or TeO 2 are not contained.

[0064] The glass of the present invention preferably does not contain S 2- , and / or does not contain Cl - , and / or does not contain F - However, S 2- , Cl - 、F - The possibility of existing in glass in the form of impurities, fining agent residues, etc.

[0065] In the glass of the present invention, even if oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo are contained alone or in combination in small amounts, the glass will be colored and absorption will occur at specific wavelengths in the visible light region, thereby weakening the property of the present invention of improving the visible light transmittance. Therefore, it is preferably substantially free of oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo, especially for optical glasses that require transmittance at wavelengths in the visible light region.

[0066] The oxides of Th, Os, Be and Se have a tendency to be controlled in recent years as harmful chemical substances, and environmental protection measures are necessary not only in the manufacturing process of glass, but also in the processing process and the disposal after productization. Therefore, in the case of paying attention to the impact on the environment, it is preferred that they are not actually contained except for being inevitably mixed in. Thus, the optical glass does not actually contain substances that pollute the environment. Therefore, even if special environmental countermeasures are not taken, the optical glass of the present invention can be manufactured, processed and discarded.

[0067] In order to achieve environmental friendliness, the optical glass of the present invention preferably does not contain Tl2O, CdO, As2O3 and PbO.

[0068] The "does not contain" and "0%" recorded in this article means that the compound, molecule or element is not intentionally added as a raw material to the optical glass of the present invention; however, as raw materials and / or equipment for producing optical glass, there will be some impurities or components that are not intentionally added, and due to environmental dust impurities, etc., they will be contained in small amounts or traces in the final optical glass, and this situation is also within the scope of protection of the patent of this invention. In general, the content of the components referred to as "does not contain" and "0%" in this article in the actual glass is less than 20ppm.

[0069] Next, the properties of the optical glass of the present invention will be described.

[0070] <Refractive Index and Abbe Number>

[0071] The refractive index of optical glass (n d ) and the Abbe number (ν d ) Tested according to the method specified in the Chinese standard GB / T 7962.1-2010. d 、n F 、n C 、n g The refractive index of glass at wavelengths of 587.6nm, 480.0nm, 656.3nm, and 404.7nm respectively. d ) is defined as follows:

[0072]

[0073] In some embodiments, the refractive index (n d ) is 1.70 to 1.75, preferably 1.71 to 1.74.

[0074] In some embodiments, the Abbe number (ν d ) is 43 to 48, preferably 44 to 47.5.

[0075] <Shortwave Partial Dispersion and Shortwave Relative Partial Dispersion>

[0076] Short-wave partial dispersion (P g,F ) is defined as follows:

[0077]

[0078] Short-wave relative partial dispersion (ΔP g,F ) is defined as follows:

[0079] ΔP g,F =P g,F -0.6457+0.001703×v d

[0080] In some embodiments, the short-wave partial dispersion (P g,F ) is 0.5600 or less, preferably 0.5590 or less, and more preferably 0.5580 or less.

[0081] In some embodiments, the short-wave relative partial dispersion (ΔP g,F ) is -0.0075 or less, preferably -0.0080 or less, and more preferably -0.0085 or less.

[0082] <Internal Transparencyλ 80 and λ5>

[0083] The internal transmittance of glass is tested using the method described in the Chinese standard GB / T 7962.12-2010. The wavelength corresponding to the internal transmittance of a 10mm thick glass sample of 80% is defined as the internal transmittance λ 80 , the wavelength corresponding to the internal transmittance of 5% in a 10mm thick glass sample is the internal transmittance λ5.

[0084] Glass Lambda 80 The smaller the λ5 is, the higher the transmittance of the glass for short-wave visible light is, the lower the degree of color cast of the glass under visible light is, and the better the use effect is in the occasions of common imaging and lighting. The glass of the present invention has good internal color transmittance.

[0085] In some embodiments, the color transmittance λ of the glass of the present invention is 80 The wavelength is 370 nm or less, preferably 365 nm or less, and more preferably 360 nm or less.

[0086] In some embodiments, the internal transmittance λ5 of the glass of the present invention is below 330 nm, preferably below 325 nm, and more preferably below 320 nm.

[0087] <Water resistance stability>

[0088] The powder method described in the Chinese standard GB / T 17129 was used to test the percentage of glass leaching under water. The glass water resistance stability (R W ) are divided into 6 categories.

[0089] Table 1.

[0090]

[0091] The glass of the present invention has good water resistance stability. In some embodiments, the water resistance stability (R W ) is Class 1 and the water leaching resistance percentage is less than 0.04%, preferably the water resistance stability (R W ) is Class 1 and the water leaching resistance percentage is below 0.03%, and the water resistance stability (R W ) is Class 1 and the water leaching resistance percentage is less than 0.02%.

[0092] <Acid resistance stability>

[0093] The powder method described in the Chinese standard GB / T 17129 was used to test the percentage of glass leaching under the action of acid. The acid resistance stability of the glass (R A ) are divided into 6 categories.

[0094] Table 2.

[0095] category Category 1 Category 2 Category 3 Category 4 5 categories 6 categories Leaching percentage <0.20% 0.20-0.35% 0.35-0.65% 0.65-1.20% 1.20-2.20% >2.20%

[0096] In some embodiments, the acid resistance stability of the glass of the present invention is Class 4 or above, preferably Class 3 or above.

[0097] <density>

[0098] The density (ρ) of optical glass is tested according to the method specified in the Chinese standard GB / T7962.20-2010. Generally speaking, the lower the density of optical glass with the same optical properties, the more it is conducive to reducing the weight of the optical system, and is beneficial to its wearable and mechanical transmission performance.

[0099] In some embodiments, the density (ρ) of the optical glass of the present invention is 4.05 g / cm 3 Below, preferably 4.00 g / cm 3 Below, more preferably 3.95g / cm 3 the following.

[0100] <Coefficient of Thermal Expansion>

[0101] The thermal expansion coefficient of glass is tested according to the method specified in the Chinese standard "GB / T 7962.16-2010". The thermal expansion coefficient of glass mentioned in this specification is the average thermal expansion coefficient of glass in the range of -30 to 70°C and in the range of 100 to 300°C, respectively denoted as α -30~70℃ and α 100~300℃ Among them, the average thermal expansion data of -30 to 70°C is closer to the conventional use temperature of optical glass and has reference significance for application; the thermal expansion meter works stably in the range of 100 to 300°C, and the data is highly accurate, which is more suitable for comparing the thermal expansion coefficients of different glasses. In general, the lower the thermal expansion coefficient of glass, the more conducive it is for the optical element and / or optical system to resist thermal shock, improve the usable temperature range, and have better use effect.

[0102] In some embodiments, the thermal expansion coefficient (α -30~70℃ ) is 60×10 -7 / ℃ or less, preferably 58×10 -7 / °C or less, more preferably 56×10 -7 / ℃ below.

[0103] In some embodiments, the thermal expansion coefficient (α 100~300℃ ) is 70×10 -7 / ℃ or less, preferably 67×10 -7 / °C or less, more preferably 64×10 -7 / ℃ below.

[0104] <Micro Vickers Hardness>

[0105] The following method is used to test the micro Vickers hardness (H v ):

[0106] First, the glass sample was precision annealed at a holding temperature of 560°C for 20 hours. After the insulation was completed, the glass sample was cooled to 440°C at a cooling rate of -4°C / h, and then cooled to room temperature at a cooling rate not higher than -50°C / h. The glass was processed into a large-surface polished sample of 40×30×10mm in size and tested using a microhardness tester. The indenter was a four-sided pyramid Vickers hardness standard indenter with a vertex angle of 135°. The applied force of the test was 2N, and the force was maintained for 10s. The relationship between the test conditions and the Vickers hardness indentation is established by the following formula:

[0107]

[0108] Where F is the test force and d is the average length of the two diagonal lines of the cross indentation.

[0109] Repeat the test 9 times and take the average value as the H of the glass sample. V . Glass H V The bigger it is, the stronger its ability to resist friction and scratches is, and the better its use value is.

[0110] In some embodiments, the micro Vickers hardness (H v ) is 670×10 7 Pa or more, preferably 690×10 7 Pa or more, more preferably 710×10 7 Pa or above.

[0111] <Transition Temperature>

[0112] Transition temperature (T g ) Tested according to the method specified in the Chinese standard "GB / T 7962.16-2010".

[0113] In some embodiments, the transition temperature (T g ) is 540 to 630°C, preferably 550 to 620°C, more preferably 560 to 610°C.

[0114] <Anti-thermal forming devitrification performance>

[0115] The anti-thermal forming crystallization performance described in this specification refers to the ability of glass to resist crystallization during the secondary thermal forming process. The test method is: cut the glass to be tested into samples of 20×20×10mm, place them in a muffle furnace kept at 780℃, take them out after a certain period of time, and observe with the naked eye and / or with a microscope whether there are crystallization particles inside the glass under the irradiation of a laser pen. According to the classification method shown in Table 3 below, the anti-thermal forming crystallization performance of glass is divided into 5 categories:

[0116] Table 3.

[0117]

[0118] The glass of the present invention has good anti-thermal forming crystallization performance. In some embodiments, the anti-thermal forming crystallization performance of the glass of the present invention is 3 or more, preferably 2 or more, preferably 1.

[0119] <Anti-crystallization performance>

[0120] The anti-crystallization performance described in this specification characterizes the difficulty of crystal precipitation in the glass during the preparation of glass by the melting method. The stronger the anti-crystallization performance, the less likely it is to crystallize during the preparation of the glass, and the more suitable it is for industrial production.

[0121] The anti-crystallization performance of the glass of the present invention is determined by the thermal insulation method of a gradient temperature furnace. Glass without inherent defects is placed in a gradient temperature furnace with a temperature distribution in the range of 900 to 1300°C. After insulation for 4 hours, it is taken out and the junction between the crystallization area and the non-crystallization area of ​​the glass is observed. The temperature of the gradient temperature furnace at the junction is recorded. According to the temperature value, the anti-crystallization performance of the glass is divided into 5 categories as shown in Table 4 below:

[0122] Table 4.

[0123] Classification criteria describe Category 1 Interface temperature <1100℃ Category 2 The junction temperature is 1100-1150℃ Category 3 The junction temperature is 1150-1200℃ Category 4 The junction temperature is 1200-1250℃ 5 categories Interface temperature>1250℃

[0124] In some embodiments, the anti-crystallization performance of the glass of the present invention is Class 3 or above, preferably Class 2 or above.

[0125] <Clarifying temperature>

[0126] The temperature corresponding to the glass viscosity of 100 Poise is defined as the glass clarification temperature. A low glass clarification temperature is beneficial to reducing energy consumption during the glass production process, reducing the erosion of refractory materials and platinum, and has more economic value.

[0127] In some embodiments, the clearing temperature of the glass of the present invention is 1260°C or lower, preferably 1240°C or lower, and more preferably 1220°C or lower.

[0128] <Bubble Degree>

[0129] The bubble degree of glass is tested according to the method specified in the Chinese standard "GB / T 7962.8-2010".

[0130] In some embodiments, the bubble degree of the glass of the present invention is A0 or above, preferably A 00 class.

[0131] [Method for producing optical glass]

[0132] The optical glass of the present invention can be prepared by a conventional melting method. Specifically, oxides, hydroxides, fluorides, hydrates, various salts (carbonates, nitrates, sulfates, phosphates, metaphosphates), boric acid, etc. are used as raw materials, fully mixed according to a set ratio, and then put into a chamber composed of platinum or refractory materials at a set temperature. After a certain period of stirring, bubbling, and standing, the above raw materials undergo a solid phase reaction, melting, and homogenization process to form a uniform glass liquid. Afterwards, the glass of the present invention can be formed into any usable shape by single crucible casting and / or leaking molding.

[0133] The glass of the present invention has good glass forming properties, and those skilled in the art can obtain the preferred production process of the glass of the present invention after limited experiments. In some embodiments, the process temperature of the glass of the present invention is 1100-1300°C, preferably 1125-1275°C, and more preferably 1150-1250°C.

[0134] [Glass preforms and optical components]

[0135] A glass preform can be made from the produced optical glass by means of grinding, or by means of compression molding such as re-hot pressing, precision stamping, etc. That is, a glass preform can be made by mechanical processing such as grinding and polishing the optical glass, or by making a preform for compression molding from the optical glass, re-hot pressing the preform and then grinding the preform to make a glass preform, or by precision stamping the preform made by grinding. It should be noted that the means for preparing the glass preform are not limited to the above means.

[0136] As described above, the optical glass of the present invention is useful for various optical elements and optical designs, and it is particularly preferred to form a preform from the optical glass of the present invention, and use the preform to perform re-hot pressing, precision stamping, etc. to make optical elements such as lenses and prisms. The glass of the present invention can also be manufactured by a one-time drop molding method.

[0137] The glass preform and the optical element of the present invention are both formed of the optical glass of the present invention. The glass preform of the present invention has the excellent properties of optical glass; the optical element of the present invention has the excellent properties of optical glass, and can provide various optical elements such as lenses and prisms with high optical value. Examples of lenses include various lenses such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses, which have spherical or aspherical lens surfaces.

[0138] [Optical instruments]

[0139] The optical glass or optical element formed by the optical glass of the present invention can be used to make optical instruments such as photographic equipment, video equipment, display equipment and monitoring equipment. The optical glass or optical element of the present invention is suitable for vehicle-mounted lighting instruments, optical equipment, and is applied to the fields of vehicle-mounted and the like. The optical glass or optical element of the present invention is suitable for optical instruments such as micro-projection, micro-imaging (video / photography), and micro-illumination.

[0140] Example

[0141] <Optical Glass Example>

[0142] In order to further clearly illustrate and describe the technical solutions of the present invention, the following non-limiting examples are provided.

[0143] This embodiment adopts the above optical glass manufacturing method to obtain optical glasses having the compositions shown in Tables 5 to 8. In addition, the properties of each glass are measured by the testing method described in the present invention, and the measurement results are shown in Tables 5 to 8.

[0144] Table 5.

[0145]

[0146]

[0147] Table 6.

[0148]

[0149]

[0150] Table 7.

[0151]

[0152]

[0153] Table 8.

[0154]

[0155]

[0156] <Glass Preform Example>

[0157] The glasses obtained from optical glass embodiments 1 to 24 are used, for example, by grinding processing, or by molding methods such as hot pressing, precision stamping, etc., to make preforms of various lenses, prisms, etc., such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses.

[0158] <Optical Element Embodiment>

[0159] The preforms obtained in the above-mentioned glass preform embodiments are annealed to reduce the deformation inside the glass and perform fine adjustments so that the optical properties such as the refractive index reach the desired values.

[0160] Next, each preform is ground and polished to produce various lenses and prisms such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. The surface of the obtained optical element may be coated with an anti-reflection film.

[0161] <Optical Instrument Embodiment>

[0162] The glass elements made from the above-mentioned glass element embodiments are optically designed to form optical components or optical assemblies using one or more glass elements, and can be used in, for example, imaging equipment, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, photolithography technology, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices including such circuits and chips, or in camera equipment and devices in the automotive field.

Claims

1. Optical glass, characterized in that: Its components, expressed in weight percentage, include: SiO2: 3-15%; B2O3: 24-34%; La2O3: 1-12%; Y2O3: 7-16%; ZnO: 20-30%; ZrO2: 3-9%; Nb2O5: 1-6%.

2. The optical glass according to claim 1, characterized in that: Its components, expressed in weight percentage, also contain: Al2O3: 0-8%; and / or Gd2O3: 0-12%; and / or Li2O: 0-4%; and / or Na2O: 0-5%; and / or K2O: 0-5%; and / or MgO: 0-5%; and / or CaO: 0-5%; and / or SrO: 0-5%; and / or BaO: 0-4%; and / or Ta2O5: 0-5%; and / or WO3: 0-3%; and / or Sb2O3: 0-0.5%.

3. Optical glass, characterized in that: Its components, expressed in weight percentage, are SiO2: 3-15%; B2O3: 24-34%; La2O3: 1-12%; Y2O3: 7-16%; ZnO: 20-30%; ZrO2: 3-9%; Nb2O5: 1-6%; Al2O3: 0-8%; Gd2O3: 0-12%; Li2O: 0-4%; Na2O: 0-5%; K2O: 0-5%; MgO: 0-5%; CaO: 0-5%; SrO: 0-5%; BaO: 0-4%; Composition: Ta2O5: 0~5%; WO3: 0~3%; Sb2O3: 0~0.5%.

4. The optical glass according to any one of claims 1 to 3, characterized in that , its components are expressed in weight percentage, wherein: Al2O3+B2O3+SiO2 is 35-45%, preferably Al2O3+B2O3+SiO2 is 36-44%, and more preferably Al2O3+B2O3+SiO2 is 37-43%.

5. The optical glass according to any one of claims 1 to 3, characterized in that , its components are expressed in weight percentage, wherein: B2O3 / (SiO2+Al2O3) is 1.5-4.0, preferably B2O3 / (SiO2+Al2O3) is 1.6-3.8, and more preferably B2O3 / (SiO2+Al2O3) is 1.8-3.

6.

6. The optical glass according to any one of claims 1 to 3, characterized in that , wherein the components are expressed in weight percentage, wherein: (Al2O3+ZrO2) / (Al2O3+B2O3+SiO2) is 0.085-0.375, preferably (Al2O3+ZrO2) / (Al2O3+B2O3+SiO2) is 0.100-0.325, and more preferably (Al2O3+ZrO2) / (Al2O3+B2O3+SiO2) is 0.125~0.

300.

7. The optical glass according to any one of claims 1 to 3, characterized in that , its components are expressed in weight percentage, wherein: Y2O3 / (2×ZnO+B2O3) is 0.090~0.210, preferably Y2O3 / (2×ZnO+B2O3) is 0.110~0.205, and more preferably Y2O3 / (2×ZnO+B2O3) is 0.130~0.

200.

8. The optical glass according to any one of claims 1 to 3, characterized in that , its components are expressed in weight percentage, wherein: Gd2O3+Y2O3 is 13-22%, preferably Gd2O3+Y2O3 is 14-21%, and more preferably Gd2O3+Y2O3 is 15-20%.

9. The optical glass according to any one of claims 1 to 3, characterized in that , its components are expressed in weight percentage, wherein: (2×Li2O+SiO2) / ZrO2 is 0.800~5.0, preferably (2×Li2O+SiO2) / ZrO2 is 0.850~4.5, and more preferably (2×Li2O+SiO2) / ZrO2 is 0.900~4.

0.

10. The optical glass according to any one of claims 1 to 3, characterized in that , wherein the components are expressed in weight percentage, wherein: (Nb2O5+Ta2O5+WO3) / (La2O3+ZrO2) is 0.05 to 0.65, preferably (Nb2O5+Ta2O5+WO3) / (La2O3+ZrO2) is 0.05 to 0.55, and more preferably (Nb2O5+Ta2O5+WO3) / (La2O3+ZrO2) is 0.05~0.

45.

11. The optical glass according to any one of claims 1 to 3, characterized in that , the components are expressed in weight percentage, wherein: SiO2: 4-14%, preferably SiO2: 5-13%; and / or B2O3: 25-33%, preferably B2O3: 26-32%; and / or La2O3: 2-10%, preferably La2O3: 3-8%; and / or Y2O3: 8-15%, preferably Y2O3: 9-14%; and / or ZnO: 21-28%, preferably ZnO: 22-26%; and / or ZrO2: 3.5-8.5%, preferably ZrO2: 4-8%; and / or Nb2O5: 1.5-5.5%, preferably Nb2O5: 2-5%; and / or Al2O3: 0.5-6%, preferably Al2O 3: 1-4%; and / or Gd2O3: 0.5-9%, preferably Gd2O3: 1-6%; and / or Li2O: 0.05-3%, preferably Li2O: 0.1-2%; and / or Na2O: 0-3%, preferably Na2O: 0-1%; and / or K2O: 0-2%; and / or MgO: 0-2%; and / or CaO: 0-2%; and / or SrO: 0-2%; and / or BaO: 0-3%, preferably BaO: 0-2%; and / or Ta2O5: 0-2%; and / or WO3: 0-1.5%, preferably WO3: 0.1-1%; and / or Sb2O3: 0-0.3%, preferably Sb2O3: 0-0.2%.

12. The optical glass according to any one of claims 1 to 3, characterized in that , the optical glass does not contain K2O; and / or does not contain MgO; and / or does not contain CaO; and / or does not contain SrO; and / or does not contain Ta2O5; and / or does not contain Bi2O3; and / or does not contain TiO2; and / or does not contain P2O5; and / or does not contain GeO2; and / or does not contain TeO2; and / or does not contain Tl2O; and / or does not contain CdO; and / or does not contain As2O3; and / or does not contain PbO; and / or does not contain Cl - ; and / or does not contain F - ; and / or does not contain S 2- .

13. The optical glass according to any one of claims 1 to 3, characterized in that , the refractive index n of the optical glass d 1.70 to 1.75, preferably 1.71 to 1.74; and / or Abbe number ν d 43 to 48, preferably 44 to 47.5; and / or short-wave partial dispersion P g,F is 0.5600 or less, preferably 0.5590 or less, more preferably 0.5580 or less; and / or the short-wave relative partial dispersion ΔP g,F It is -0.0075 or less, preferably -0.0080 or less, and more preferably -0.0085 or less.

14. The optical glass according to any one of claims 1 to 3, characterized in that , the λ of the optical glass 80 is 370nm or less, preferably 365nm or less, more preferably 360nm or less; and / or λ5 is 330nm or less, preferably 325nm or less, more preferably 320nm or less; and / or water resistance stability R W Class 1 and the water leaching resistance percentage is less than 0.04%, preferably Class 1 and the water leaching resistance percentage is below 0.03%, more preferably Class 1 and the water leaching resistance percentage is below 0.02%; and / or acid resistance stability R A 4 or more, preferably 3 or more; and / or density ρ is 4.05 g / cm 3 Below, preferably 4.00 g / cm 3 Below, more preferably 3.95g / cm 3 Below; and / or thermal expansion coefficient α -30~70℃ 60×10 -7 / ℃ or less, preferably 58×10 -7 / °C or less, more preferably 56×10 -7 / ℃ or below; and / or thermal expansion coefficient α 100~300℃ 70×10 -7 / ℃ or less, preferably 67×10 -7 / °C or less, more preferably 64×10 -7 / ℃ or below; and / or micro Vickers hardness H v 670×10 7 Pa or more, preferably 690×10 7 Pa or more, more preferably 710×10 7 Pa or above; and / or transition temperature T g The temperature is 540-630°C, preferably 550-620°C, more preferably 560-610°C; and / or the anti-thermal forming crystallization performance is 3 or more, preferably 2 or more, more preferably 1; and / or the anti-crystallization performance is 3 or more, preferably 2 or more; and / or the bubble degree is A0 or more, preferably A 00 and / or a refining temperature of 1260°C or less, preferably 1240°C or less, more preferably 1220°C or less.

15. A glass preform, characterized in that , made of the optical glass described in any one of claims 1 to 14.

16. An optical element, characterized in that , made of the optical glass described in any one of claims 1 to 14 or the glass preform described in claim 15.

17. An optical instrument, characterized in that , containing the optical glass according to any one of claims 1 to 14, or containing the optical element according to claim 16.

Citation Information

Cited By

  • Automobile lens optical glass preform and preparation method thereof

    CN120117830A

  • Optical glass, preparation method thereof and optical element

    CN120794334A